e-infrastructure and e-services for developing countries : 5th International Conference, AFRICOMM 2013, Blantyre, Malawi, November 25-27, 2013, Revised Selected Papers - van Stam, Gertjan; Bissyande, Tegawende F. (Lecture Notes of the Institute for Computer Sciences, Social Informatics and Telecommunications Engineering, 2014)
This book constitutes the thoroughly refereed proceedings of the 5th International Conference on e-Infrastructure and e-Services for Developing Countries, AFRICOMM 2013, held in Blantyre, Malawi, in November 2013. The 32 revised full papers presented were carefully reviewed and selected from 94 submissions. The papers discuss issues and trends, resent research, innovation advances and on-the-field experiences related to e-governance, e-infrastructure, and e-business with a focus on developing countries.